Proceedings of the Ninth ACM Conference on Data and Application Security and Privacy 2019
DOI: 10.1145/3292006.3300043
|View full text |Cite
|
Sign up to set email alerts
|

Verifiable Round-Robin Scheme for Smart Homes

Abstract: Advances in sensing, networking, and actuation technologies have resulted in the IoT wave that is expected to revolutionize all aspects of modern society. This paper focuses on the new challenges of privacy that arise in IoT in the context of smart homes. Specifically, the paper focuses on preventing the user's privacy via inferences through channel and in-home device activities. We propose a method for securely scheduling the devices while decoupling the device and channels activities. The proposed solution a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As mentioned in Section I, the increasing growth of IoT applications raises several user privacy concerns such as unauthorized access to their personal information or lack of detailed Developing privacy setting interfaces. [51], [54], [56], [17], [19], [18], [54], [67], [77], [52], [65], [53].…”
Section: User Studies and Survey-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in Section I, the increasing growth of IoT applications raises several user privacy concerns such as unauthorized access to their personal information or lack of detailed Developing privacy setting interfaces. [51], [54], [56], [17], [19], [18], [54], [67], [77], [52], [65], [53].…”
Section: User Studies and Survey-based Approachesmentioning
confidence: 99%
“…In addition, previous research has shown that inference of personal information is possible by analyzing data from single IoT devices or by monitoring traffic data from several active intelligent devices within a network [? ], [52], [168]. However, as discussed above, limited focus has been given to investigating the inference risk of personal information in a heterogeneous IoT environment and multi-functional IoT devices.…”
Section: B Opportunities For Future Workmentioning
confidence: 99%
“…• Different Time and Same Space: This use-case requires scheduling protocols [3] such that devices receive an actuation token, perform computation, produce results, and pass the token to next device in the queue. In [11] we present a new verifiable delay scheme that allows an unpredictable amount of artificial delay before the command actuation at any home device. In particular, our solution provides improved privacy guarantees over naive solutions that require command pre-scheduling at these IoT devices.…”
Section: Proximity Modelmentioning
confidence: 99%

Smart Home Survey on Security and Privacy

Panwar,
Sharma,
Mehrotra
et al. 2019
Preprint
Self Cite
“…Supporting such fine grained policies raises several significant challenges that are beginning to attract research attention. These challenges include policy languages suitable for representing data capture, processing, sharing, and retention policies [28] together with mechanisms for users to specify their choices within the system. This paper addresses one such challenge: scaling enforcement of access control policies in the context of database query processing when the set of policies becomes a dominant factor/bottleneck in the computation due to their large number.…”
Section: Introductionmentioning
confidence: 99%